Examining the Relationship between Life Satisfaction and the Happiness-increasing Strategies used by Mothers for their Children - İlknur Tarman; Cicek Eminanc (Research in Social Sciences and Technology- OpenED Network, 2023)
The aim of this research is to reveal the relationship between the life satisfaction of mothers and the happiness-increasing strategies they use for their children. Within the scope of the general purpose of the study, it was also examined whether the life satisfaction of the mothers and the happiness-enhancing strategies they used for their children differed in terms of some demographic variables. The correlational model, one of the quantitative research designs, was used in the study, and the sample group consisted of 298 mothers with children aged 3-5 years. A Demographic Information Form, a Scale for Determining Happiness-increasing Strategies Used by Mothers, and a Life Satisfaction Scale were used as data collection tools. In the research; t test and single-factor analysis of variance (ANOVA) were performed for independent samples with differentiation tests to examine the differences between the life satisfaction levels of the mothers and the happiness-increasing strategies they applied according to variables such as education level, economic status, and working status. Pearson moments multiplication correlation analysis was performed to examine the relationship between mothers' life satisfaction levels, happiness-increasing strategy levels, age of mothers, and child age, and multiple linear regression analysis was performed to determine the predictive power of the independent variable (happiness-enhancing strategies) to the dependent variable (life satisfaction). At the end of the research, it was concluded that the level of life satisfaction increased as the education level and economic status of the mothers increased, and the levels of happiness-increasing strategies showed a significant difference according to the economic status. It was seen that there was a significant relationship between the life satisfaction levels of the mothers and the strategies to increase happiness. Recommendations were developed in line with the findings obtained as a result of the research.